Nowe stanowisko Paracymus aeneus (Germar, 1824) (Coleoptera: Hydrophilidae) w Polsce - Czesław Greń; Aleksandrowicz, Oleg; Lubecki, Krzysztof (Zenodo, 2021)
New locality of Paracymus aeneus (Germar, 1824) (Coleoptera: Hydrophilidae) in Poland. Paracymus aeneus has been previously recorded in Poland based on a single finding published in 2006, on inland salt marsh surrounding salty springs in the Kołobrzeg. The paper presents the second locality of Paracymus aeneus in Poland. : {"references": ["Burakowski B., Mroc zkowski M., Stefa\u0144ska J. 1973. Chrz\u0105szcze \u2013 Coleoptera. Biegaczowate \u2013 Carabidae 1. Katalog fauny Polski 23(2), PWN, Warszawa.", "Fik\u00e1\u010dek M., Angus R.B., Gentili E., Jia F., Minoshima Y.N., Prokin A., Przewo\u017any M., Ryndevich S.K. 2015. Family Hydrophilidae, pp. 37\u201376, In: L\u00f6bl I. & L\u00f6bl D. (Eds.), Catalogue of Palaearctic Coleoptera. Vol. 2/1. Hydrophiloidea \u2013 Staphilinoidea. Revised and updated edition. Brill, Leiden-Boston.", "Hansen M. 1987. The Hydrophiloidea (Coleoptera) of Fennoscandia and Denmark. Fauna Entomologica Scandinavica 18: 1\u2013254.", "Przewo\u017any M. 2021. Catalogue of Palearctic Hydrophiloidea (Coleoptera). Internet version 2021-01-01.", "Ruta R., Stachowiak M., Aleksandrowicz O. 2006. The first record of Paracymus aeneus (Germar, 1824) (Coleoptera: Hydrophilidae) in Poland with notes on halophilous and halobiontic Hydrophilidae and Hydraenidae in Polish fauna. Polskie Pismo Entomologiczne 75(3): 359\u2013368."]}